Ancient muses : archaeology and the arts - Jameson, John H.; Ehrenhard, John E.; Finn, Christine, 1959- (University of Alabama Press, 2003)
Known widely in Europe as ""interpretive narrative archaeology, "" the practice of using creative methods to interpret and present current knowledge of the past is gaining popularity in North America. This book is the first compilation of international case studies of the various artistic methods used in this new form of education-one that makes archaeology ""come alive"" for the nonprofessional. Plays, opera, visual art, stories, poetry, performance dance, music, sculpture, digital imagery-all can effectively communicate archaeological processes and cultural values to public audience